Congenital Esophageal Atresia with Tracheo – Esophageal Fistula - Muhieldeen, Samir A. (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2008)
The records of patients with congenital esophageal atresia with tracheo– esophageal fistula at al kadhymia teaching hospital between 2004–2007 were reviewed and studied. This comprised 25 patients (10) were male and (15) were female (M/F= 2/3). According to waterston classification, the commonest type was type (A) 18 cases. The basic principles in the assessment and the way of management which are adopted in our department are outlined; all were subjected to correction and primary anastomosis with hospital mortality rate of 16%. This study is conducted in an effort to analyze the factors responsible for this high mortality rate and to discuss problems pertaining to management.